ANALISIS TINGKAT KERAWANAN TANAH LONGSOR MENGGUNAKAN METODE FREKUENSI RASIO DI DAERAH ALIRAN SUNGAI BIALO - Nurul Fadilah; Usman Arsyad; Andang Suryana Soma (PERENNIAL, 2019)
Landslide is a movement of soil with slope direction and moves it on a slide. This study aimed to predict the landslide susceptibility map by using a frequency ratio. It used seven causative factors, such as slope, curvature, land use, lithology, distance to a river, distance to lineament, and rainfall. The result showed the AUC of success rate and predicted rate produced high accuracy with 0.907 and 0.904, respectively.  According to the frequency ratio, the slope was the most influential than the other causative factors with 7.15. The landslide susceptibility divided into five classes, i.e. very low, low, moderate, high, and very high.  Landslide susceptibility with very high and high was 19%.  Moreover, classes susceptibility of very low, low, and moderate were 71%. The presentation of very high and high susceptibility is low, but it was located on an upper stream, and it will be a danger if to the downstream.